Prevalence of COVID-19 outcomes in patients referred to opioid agonist treatment centers - Khani, Samira; Tafaroji, Javad; Yaghoubi, Mehdi; Emami Kazemabad, Mohammad Javad; Hejazi, Seyed Amir (Frontiers in Pharmacology, 2023)
Background: Coronavirus disease (COVID-19) is a mild to severe infectious respiratory illness caused by the SARS-CoV-2 virus. Based on the numerous pieces of evidence regarding the role of opioids in immune function, viral replication, and virus-mediated pathology, we decided to assess the incidence and severity of COVID-19 outcomes in people undergoing opioid maintenance treatment. Methods: This is a prospective, descriptive, multi-center study that included 452 patients undergoing maintenance treatment in opioid agonist treatment (OAT) clinics in different cities of Iran. Demographic information, underlying disease, history of maintenance treatment, type of drug used, history of addiction, smoking, and the kind of substance abused, were recorded. A physician evaluated the COVID-19 symptoms, and the severity of the disease was defined based on the number of observed symptoms. Results: The results have not shown any significant difference in the severity of COVID-19 symptoms in different nationalities, gender, and treatment groups. Furthermore, the history of drug abuse, including time and type of abuse and smoking, has not indicated any significant association with the occurrence of symptoms. Only the severity of COVID-19 in the mentioned cities (1st and 2nd follow-up: p <0.001) and individuals with a history of underlying disease (1st follow-up: p = 0.020; 2nd follow-up: p = 0.043) were significantly different. Conclusions: Our results have demonstrated that the severity of symptoms in people with the underlying disease was significantly higher than in others. But there is no association between sex, race, treatment groups, and abuse history with the severity of COVID-19 symptoms in methadone maintenance treatment (MMT) patients. Keywords: COVID-19, Opioid, Immunomodulation, Opioid Agonist, Methadone Maintenance Program